Composição taxonômica, funcional e molecular da microbiota planctônica: integrando diferentes níveis tróficos na ecologia aquática - Machado, Karine Borges (2019)
The aquatic microbiota play an important role in the ecosystems functioning. However, the factors that are associated with the structuring of microbiological communities as well as their responses to climate change are still not well understood. In addition, most evaluations do not consider the effects on different trophic levels simultaneously. This study aimed to associate taxonomic, functional and molecular knowledge on aquatic microorganisms, seeking to investigate the causes of the diversity geographic patterns as well as their responses to global warming. This work was carried out using data from 27 lakes in the Araguaia river floodplain and also by the construction of an experiment in microcosm. We found that environmental and spatial factors do not influence planktonic microbiota 18S rDNA in the lakes evaluated, although there is a high beta diversity and the composition is spatially structured along the plain. On the other hand, we found that experimentally simulated warming promotes a change in the taxonomic and functional composition of planktonic organisms, due to a species substitution and a predominance of smaller organisms. Furthermore, the microbiota of different trophic levels presents a similar response pattern to warming. These results contribute to predict how different biological levels and trophic groups of the aquatic microbiota respond to variations in environmental conditions. We highlight that this approach is relevant, because changes in the composition of communities can affect many ecosystem processes and services.